Customers’ emotional reactions as significant predictors towards excellent customer service experiences / Anizah Zainuddin and Shereen Noranee - Zainuddin, Anizah; Noranee, Shereen (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2017)
This study examines the role of customers‟ emotional reactions in the context of customer service experiences. It investigates how retail banking customers‟ emotional responses to retail banking services to affect their overall banking experience. In the context of retail banking, excellent customer service experiences could be interpreted as just meeting the expectations of the retail banking customers, not any sort of exceeding of failing short of the expectations. Most of the banks try to achieve competitive advantage by taking the responses of the retail banking customers beyond the level of „just service satisfied‟ towards „exceeding their service expectations‟. Therefore, this study attempts to fill this gap by examining the relationship between customers‟ emotional reactions and excellent customer service experiences in banking sector. Structured questionnaires were distributed to 320 retail banking customers using purposive sampling technique in the area of Klang Valley. The instruments used for data collection for all variables in the study includes bank image, emotional reactions, bank service quality value, personal contact value and excellent customer service experiences were adapted from various studies using five point likert scale. The results suggest that emotional reactions, bank service quality value and personal contact value had a moderate relationship with excellent customer service experiences. This study identifies the types of efforts that can be implementing in helping banking sector caused by retail banking customers‟ emotional responses.